The solar system our neighbors in space - Hildebrant, Jeff; Beers , Theresa; Broadwater, Hillary; Great Pacific Media (Chatsworth, CA : AIMS Multimedia, 1997)
An examination of the origins of the solar system and the geology , climate , atmosphere and moons of each
Keywords: Solar System -- Juvenile films; Astronomy -- Juvenile films; Planets -- Juvenile films; Asteroids -- Juvenile films